Comparison of microvessel density and PSA level in prostatic adenocarcinoma of Gleason score 6 and 7: Primerjava gostote malih žil in vrednosti PSA pri adenokarcinomih prostate z oceno 6 in 7 po Gleasonu - Dariš, Barbara; Munda, Miha; Hajdinjak, Tine; Kavalar, Rajko; Štiblar-Martinčič, Draga (Acta Medico-Biotechnica, 2021)
Purpose: The aim of our investigation was to determine differences in microvessel density (MVD) and serum levels of prostate-specific antigen (PSA) between groups of patients with Gleason score (GS) 6 adenocarcinoma and patients with GS 7 adenocarcinoma.Methods: The study was done in a series of 26 patients with prostatic adenocarcinoma. Specimens were divided into two groups: GS 6 (13 cases) and GS 7 (13 cases). Intratumoral microvasculature was highlighted by immunohistochemical means using an antibody against endoglin. Endoglin stained microvessels in and around the tumor but showed weak or no staining for bloodvessels in non-neoplastic tissue. Areas of maximal angiogenesis within the tumor were identified and microvessels counted at ×400 magnification (0.19 mm2 field).Results: The GS 6 group had lower MVD per field(19.9 vs. 25.6; P=0.05) and MVD per mm2 (89.7 vs. 117.7; P=0.05) when compared with the GS 7 group. No significant difference in mean serum levels of PSA between the two groups was observed (5.7 vs. 10.2 ng/ mL; P=0.10). MVD per mm2 was not correlated with PSA (r=0.20; P=0.30). The age of patients at diagnosis was significantly lower in cases with GS 6 prostatic adenocarcinoma (61.2 vs. 66.2 years; P=0.01).Conclusion: Our preliminary results suggest a possible difference in the neovascularization between the two groups of specimens, but a difference in PSA level was not proved. Nevertheless, a future large-scale study is needed to confirm these findings.